Legal Framework for Implementation of m-Government in Ethiopia: Best Practices and Lessons Learnt - Woldehanna, Frehiwot; Mulugeta, Wondwossen; Getaneh, Samuel; Debebe, Mulugeta (Zede Journal of Ethiopian Engineers and Architects, 2023)
Higher penetration of mobile services in many countries, including Ethiopia, makes m-Government an eminent technological option for delivering government services to public and businesses. Although the Ethiopian government has introduced e-government services to the public, the legal framework to support such services is yet to be ratified. The absence of such a ratified legal framework is one of the reasons for the delay in implementing the intended government services via m-government. In this paper, a situation analysis of the Ethiopia case and the experiences of other countries including Korea, the leading example in m-Government, are reviewed to analyze the existing situation in Ethiopia. The objective of the thematic research which is to recommend the necessary amendments for the legal framework developed for e-Government initiatives